Peran Pelatihan Keterampilan Medik dan Kepaniteraan Klinik terhadap Kelulusan OSCE UKDI - Cecilia Felicia Chandra; Fundhy Sinar Ikrar Prihatanto; Nancy Margarita Rehatta (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2015)
Background: One of the areas of competence expected from a doctor in Indonesia is clinical skills. It will be assessed in the National Objective Structured Clinical Examination (OSCE). In the Faculty of Medicine Airlangga University, there are four clinical skill modules in second to fifth semester. Afterward, students go to clinical posting to apply their clinical skill and practice profesionalism to real patients. The objective of this study is to measure the correlation between clinical skill examination score, educational environment, and Grade Point Average (GPA) during clinical posting and National OSCE’s score.Method: This study used cross sectional approach. Data were obtained from 143 national OSCE’s participant. Primary data obtained from clinical posting’s educational environment questionnaire. Secondary data consisted of five categorized scores from clinical skill examination during preclinic; clinical posting GPA; and National OSCE’s scores. We conducted three different analyses: Spearman correlation test to measure the correlation of clinical skills examination scores to National OSCE’s scores; Pearson correlation test to measure the correlation of clinical posting GPA to OSCE’s scores; and correlation of clinical posting’s questionnaire to OSCE’s scores.Results: Clinical skills examination score was weakly correlated with OSCE’s score (r= 0,189, p< 0,05). Clinical posting GPA was also correlated with OSCE’s score (r= 0,417, p<0,001). But, there was no correlation of clinical posting’s educational environment with OSCE’s score (p>0,05).Conclusions: There is a correlation between clinical skills examination scores and academic achievement during clinical posting with OSCE’s score. But, there is no correlation between clinical posting’s educational environment with OSCE’s score.